2015
DOI: 10.1111/cid.12337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insertion Torque on the Clinical Outcome of Single Implants: A Randomized Clinical Trial

Abstract: The findings suggested that implants inserted with high-IT (≥50 Ncm) in healed bone ridges showed more peri-implant bone remodeling and buccal soft tissue recession than implants inserted with a regular-IT (<50 Ncm). Moreover, sites with a thick buccal bone wall (≥1 mm) - after implant osteotomy site preparation - seemed to be less prone to buccal soft tissue recession after 12 months than sites with a thin buccal bone wall (<1 mm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 23 publications
3
83
1
Order By: Relevance
“…This factor may have also contributed to stabilization of CBL. Moreover, it has been shown that implants with an insertion torque of <50 Ncm maintain crestal bone levels 40 , 41 . In the present study, all implants were placed using insertion torques ranging from 30 to 35 Ncm.…”
Section: Discussionmentioning
confidence: 81%
“…This factor may have also contributed to stabilization of CBL. Moreover, it has been shown that implants with an insertion torque of <50 Ncm maintain crestal bone levels 40 , 41 . In the present study, all implants were placed using insertion torques ranging from 30 to 35 Ncm.…”
Section: Discussionmentioning
confidence: 81%
“…The presence of bone loss and probing depth alone may not be enough to formulate a diagnosis of peri-implantitis: bone loss can have a number of non-bacterial causes including surgical technique [65], implant design [66], implant positioning [67], crestal bone thickness [68,69] or occlusal overload [70]. For this reason, we excluded a consistent number of studies (although included in recent reviews [7-9,61,71,72]), which were reporting only data concerning bone loss around implants, without giving a definite diagnosis of peri-implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…The 50 N cm value is an important reference point according to recent evidence reported by Barone et al, [11] who observed that implants inserted with high-insertion torque (50 N cm) in healed bone ridges showed more peri-implant bone remodelling and buccal soft-tissue recession than implants inserted with a regular-IT (<50 N cm).…”
Section: Resultsmentioning
confidence: 93%
“…However, controlled values of the insertion torque are needed in order to not increase bone remodelling around the implants and possibly lead to a resorption of most coronal threads. [11] In post-extraction sites, the anatomy itself is not favourable for faster achievement of primary stability and osseointegration.…”
Section: Resultsmentioning
confidence: 99%